Theoretical investigation of flow over a cavity - Satishkumar Kurusamy. (2009)
How the vortex mechanism works is a problem in the area of fluid dynamics. This problem may arise in the area of aeronautics when there are bomb bays, open cockpits or escape hatches which act as cavities in the direction of the flow. This study focuses on the modeling Vortices are usually unsteady and this makes experimental analysis on them generally difficult. Thus, a theoretical study is a more relevant way of analyzing its mechanisms. The scope of this project is the study of fluid flow over different types of edges and these edges were combined to produce cavities of different geometries. The interactions of vortices with these geometries were then studied. The vortices were modeled by combining potential flows and converting them through a transformation into a physical plane. Different transformations were used to produce different edge shapes as well as cavity types. From the study, it was shown that a circular shaped edge will result in a smoothest vortex trajectory, followed by a plate edge and an elliptical edge. A higher starting position of a vortex was found to minimize the effect of the interaction edge. Having two and three vortices within the cavity was shown to result in chaotic trajectories. In the case of two vortices, having the starting points of the two vortices close to each other resulted in more entanglement of the trajectories. Having greater distance between the vortices resulted in less interaction between the vortices. Finally, the effect of rounding of the trailing edge was that the flow over the trailing edge became smoother as it took the shape of the curve of the edge.In conclusion, the effect of different edges and cavity types were studied and their effects were shown and this will allow for specific areas to be targeted in future studies.